An Implementation of Anger Expressive Speech in the Film Kapan Pindah Rumah? - Rahmawati Sartika; Irwan Suswandi (Raja Zulkarnain Education Foundation, 2025)
This study is a descriptive qualitative study that aims to examine the use of speech in expressing anger in the film Kapan Pindah Rumah? using Roman Jakobson’s theory of language function (1960). The research data consists of seven scenes depicting conflicts between a mother and her children. Data collection was conducted using the simak method through basic sadap techniques, simak bebas libat cakap techniques, and catat techniques. Data analysis used the matching method with advanced ortografis and padan pragmatis methods. The results showed that angry emotions were expressed through the choice of confrontational words, the use of negative imperatives, repetition, high intonation, and nonverbal gestures such as pointing, staring, and shooing. Based on Jakobson’s theory, dominant angry utterances represent the emotive function as an outburst of feelings and the conative function to influence the interlocutor. The findings from these seven scenes confirm that utterances play an important role not only as a means of communication but also as a tool for control, emotional expression, and negotiation of power relations within the family.